Fenomena Gender Digital Divide pada Wirausaha Wanita di Surabaya yang Menggunakan E-Commerce dengan Pendekatan UTAUT - Suryawirawan, Okto Aditya; Suhermin, Suhermin; Zahro, Mar'atus; Rahayu, Rika (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.12.TAHUN.2024DO - 10.24843/EEB.2024.v13.i12.p11, 2025)
Very few studies analyze the use of e-commerce applications by female entrepreneurs. This study aims to analyze the use of female entrepreneurial e-commerce using the UTAUT concept. The study was conducted on women entrepreneurs in Surabaya using a non-probability purposive sampling method. Based on a questionnaire distributed directly to women entrepreneurs through Google Form, 85 women entrepreneurs engaged in food and beverage were collected. The collected data was processed using the Partial Least Square (PLS) analysis method through SmartPLS software. Performance expectancy, effort expectancy, and facilitating conditions did not significantly affect the e-commerce use intention. Social influence has a significant positive effect on e-commerce use intention. Age and usage experience cannot moderate the impact of performance expectancy, effort expectancy, social influence and facilitating conditions on e-commerce use intention. This study shows that the gender digital divide does not occur in female entrepreneurs in Surabaya's food and beverage sector. MSMEs in this field must take advantage of all available applications to stay competitive, increasing the chances of being chosen by consumers actively seeking promotions through various platforms.